2011
DOI: 10.1590/s0001-37652011005000039
|View full text |Cite
|
Sign up to set email alerts
|

Elastase-induced pulmonary emphysema: insights from experimental models

Abstract: Several distinct stimuli can be used to reproduce histological and functional features of human emphysema, a leading cause of disability and death. Since cigarette smoke is the main cause of emphysema in humans, experimental researches have attempted to reproduce this situation. However, this is an expensive and cumbersome method of emphysema induction, and simpler, more efficacious alternatives have been sought. Among these approaches, elastolytic enzymes have been widely used to reproduce some characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 66 publications
2
46
0
9
Order By: Relevance
“…The PPE‐induced model is highly reproducible but does not capture all features of human emphysema (Antunes & Rocco, 2011). We also observed that cigarette smoking‐induced pulmonary dysfunction was ameliorated by the elimination of p19 ARF ‐expressing cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The PPE‐induced model is highly reproducible but does not capture all features of human emphysema (Antunes & Rocco, 2011). We also observed that cigarette smoking‐induced pulmonary dysfunction was ameliorated by the elimination of p19 ARF ‐expressing cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used model where the therapeutic potential of MSCs was studied was intratracheal instillation of pancreatic elastase into mice to induce lung damage mimicking emphysema [15]. Elastase cleaves elastin fibers, leading to a reduced elastin content, and causes alveolar lesions as seen in emphysema patients [16].…”
Section: Msc Treatment In Preclinical Models Of Emphysemamentioning
confidence: 99%
“…As formas de indução do enfisema são divididas entre os modelos de indução por cigarro e indução por elastase. Existem modelos de enfisema induzidos pela elastase que se diferenciam na dose, na quantidade de aplicações, no tempo do protocolo e na forma de aplicação (Antunes, 2011 …”
Section: Modelos Experimentaisunclassified